Efektifitas Penyelesaian Perkara Melalui E-Court Di Masa Pandemi Covid-19 Pada Pengadilan Tata Usaha Negara Palangka Raya - Wiwik Krisnawati; Danes Jaya Negara; Luluk Tri Harinie (Edunomics Journal, 2023)
The purpose of the research is to find out how the case settlement process was before the implementation of E-Court at the Palangka Raya State Administrative Court, to find out how the case settlement process was after the implementation of E-Court during the covid 19 pandemic at the Palangka Raya State Administrative Court, and to For find out what are the obstacles faced after implementing E-Court in settling cases and the efforts made by the Palangkaraya State Administrative Court to overcome these obstacles. This type of research is descriptive research with a qualitative approach, to obtain empirical data and information. The results of the study revealed that: 1) The case settlement process before the implementation of E-Court at the Palangkaraya State Administrative Court did not run effectively because it was still manual, meaning that justice seekers had to come directly to the Court's office from the registration of claims to decisions, so this was not appropriate with the principle of administering justice in a simple, fast and low cost manner; 2) The case settlement process after the implementation of E-Court during the covid - 19 pandemic at the Palangka Raya State Administrative Court is running effectively because it is no longer manual but online so that it can be done from anywhere without the need to come to the Court office thereby reducing face-to-face and avoiding crowds, the process is also simpler, faster and cheaper, besides that the performance of the court apparatus has increased, which means that the competency of the apparatus is very good; and 3) Obstacles encountered during the implementation of E-Court at the Palangkaraya State Administrative Court can be overcome properly by making various efforts to overcome them so that the implementation of E-Court continues to run effectively.